Impact of Disinvestment on Banking and Insurance Sectors - Patil, P. B.; Thakkar, P. N. (Indian Journal of Marketing, 2007)
Until 1990s, the Indian Financial System was characterized by a limited competition. Both the producers and players were circumscribed by heavy regulation in interest rates, in credit, in government securities and in capital markets. An administered structure of highly segmented market with limited competition and a few distinct alternative products characterized the Indian banking scenario. Today, the paradigm of "universal banking" is fast catching up. Banks are striving to be universal service-providers, both for the wholesale and the retail customers. Several Indian financial institutions are emulating international players like Citigroup, Bank of America, HSBC, etc., for becoming universal banks. Adopting the new paradigm are the newly started private sector banks like HDFC, ICICI, UTI, etc. Currently, they account for 4.1% share of the domestic market but their impact is tremendous. These banks occupy a niché between State-owned and foreign banks.